2007
DOI: 10.1055/s-2007-990906
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Amidation of Phenols through the Use of Hypervalent Iodine Reagents: Development and Applications

Abstract: This contribution reviews a family of reactions devised in our laboratory that effect the oxidative conversion of phenols into 4-amido-dienones. A salient feature of this chemistry is the use of hypervalent iodine reagents, especially diacetoxyiodobenzene (DIB), as uniquely capable oxidants in the context of the new transformation. The advent of this methodology has created new opportunities in alkaloid synthesis. Our efforts toward FR-901483, TAN-1251C, cylindricine C, and other nitrogenous natural products i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 199 publications
(61 citation statements)
references
References 18 publications
0
60
0
Order By: Relevance
“…The fact here, however, seemed to preclude the role of DTBMP as a nucleophile to first react with triflic anhydride. Indeed, it has been reported that due to its steric hindrance, DTBMP does not react with triflic anhydride to generate the reactive pyridinium intermediate G. [22a] Thus, although the exact role of DTBMP is not yet clear at this stage, a new plausible mechanism for the Tf 2 Oactivated addition of organometallic reagents to lactams and [3][4][5][6][7][8]. Mention should be made that to ensure complete lactam activation, the activation time may be prolonged to 2 h, or the reaction temperature may rise from À78 to 0 8C before cooling back to À78 8C for Grignard reagent addition.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The fact here, however, seemed to preclude the role of DTBMP as a nucleophile to first react with triflic anhydride. Indeed, it has been reported that due to its steric hindrance, DTBMP does not react with triflic anhydride to generate the reactive pyridinium intermediate G. [22a] Thus, although the exact role of DTBMP is not yet clear at this stage, a new plausible mechanism for the Tf 2 Oactivated addition of organometallic reagents to lactams and [3][4][5][6][7][8]. Mention should be made that to ensure complete lactam activation, the activation time may be prolonged to 2 h, or the reaction temperature may rise from À78 to 0 8C before cooling back to À78 8C for Grignard reagent addition.…”
Section: Resultsmentioning
confidence: 99%
“…Representative bioactive alkaloids containing 1-aza-A C H T U N G T R E N N U N G spirocycles are shown in Figure 1. [4] Although much effort has been made to construct such structural motif, [5,6] the transformation of lactams and amides into the corresponding tert-alkylamines by one-pot reductive bis-alkylation with different organometallic reagents (Scheme 1) is both a highly desirable and a challenging objective. [6] The merit of this transformation is also linked to the high stability of lactams/amides, the powerful directing ability of lactams/ amides for metallation [7] and C À H activation, [8] as well as the ready availability of both lactams/amides [9] and Grignard/organolithium reagents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The title compound is an intermediate in an ongoing synthetic study on Himandrine and related alkaloids [1,2]. The lattice contains two crystallographically independent molecules in the asymmetric unit, however there are no significant geometric differences between the two molecules.…”
Section: Discussionmentioning
confidence: 99%
“…This precise transformation was unknown until the late-1990s, and, indeed, it was believed not to be feasible. This lore was rooted in an important Technology for oxidative amidation of phenols finally emerged in 1998 thanks to research carried out in our own laboratories [19]. First of all, we perceived a mechanistic analogy between the formation of lactone 67 upon oxidative activation of the phenol and the results obtained by Knapp during a study of the iodoamidation of olefins [20].…”
Section: Oxidative Amidation Of Phenolsmentioning
confidence: 99%